AN ERROR ANALYSIS ON SUBJECT-VERB AGREEMENT OF WRITTEN ENGLISH BY 11th GRADE STUDENTS OF MAN 3 TULUNGAGUNG - AS'ARI, M. YUSUF (Jurnal Ilmiah Mahasiswa FIB, 2013)
In learning language, making mistakes is normal among learners, because mistakesare needed in order to give better feedback for better improvement in learning process. Oneof problem arises in learning certain language is on the grammar. Subject-verb agreement isone of basic rules in English, and learners still producing errors in producing it. From theerrors, the mastery of the language system can be identified. There are two problems to besolved, namely: (1) grammatical errors on subject-verb agreement made by 11th students ofMAN 3 Tulungagung and (2) systematicity errors on subject-verb agreement made by 11th students of MAN 3 Tulungagung.In this research, the writer uses descriptive qualitative approach because it willdescribe and explain the data from the subjects. The research meant to describe and explainsubjects’ subject-verb agreement errors and their mastery on the rules.The research reveals that all grammatical errors (omission, addition, misformation,and misordering) on subject-verb agreement and systematicity error stages (pre-systematicerror, systematic error, and post-systematic error) on subject-verb agreement are identified.For the occurrence of grammatical error on subject-verb agreement, the subjects tend to omita certain item that must be presented in order to form a correct sentence, and the errors werecaused by the fact that the subject do not know that the item must be presented. For theoccurrence of systematicity errors on subject-verb agreement, mostly the subjects’ knowledgeon subject-verb agreement is identified on systematic error stage. It means that subjects haveknown some marker (rules), although the rules are wrong.The writer suggests that the student should study more on subject-verb agreement,and the writer suggests that the teacher should give more attention to students’ grammarespecially on subject-verb agreement. The writer should realize that he should pay moreattention to his works in order to minimize errors and unnecessary mistakes, and the writersuggests the next researcher conduct a research on larger circumstance of English grammar.   Key words: Error analysis, subject-verb agreement, surface strategy taxonomy, systematicityerror.